PERAN SATUAN POLISI PAMONG PRAJA KOTA PALEMBANG DALAM PENGAWASAN, PENGENDALIAN DAN PENCEGAHAN PENYEBARAN VIRUS COVID-19 SELAMA PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) - Raden Wijaya (Fakultas Hukum Tata Pemerintahan, 2020)
The city government of Palembang in this case the mayor of Palembang has issued the Palembang Mayor's Instruction No. 1 of 2020 on April 21, 2020 which instructs the improvement of control, prevention, and handling of transmission of corona virus diseases 2019 (COVID-19) in the city of Palembang. This research aims to maintain public peace in facing the spread of COVID-19 in Indonesia conducted by the Civil Service Police Unit. The research method uses an empirical legal approach. Data collection techniques sourced from primary data and secondary data. The results showed that the Palembang City Civil Service Police Unit had tried to overcome the existing problems, it was found obstacles in the field such as the people who did not wear masks and still clustered on the grounds of family members. However, this can be handled by the PP policemen by arranging patrol schedules so that they routinely check the activities of the people with the firmness of the Sat Pol PP leaders in the city of Palembang. The commitment is supported by infrastructure to always stop appealing to the public both through print and online media. This is influenced by factors that influence the success of COVID-19 supervision, control and prevention during PSBB, including internal factors including the Palembang Municipal Civil Service Police Unit in monitoring, controlling, preventing the spread of COVID-19 always prioritizing coordination and synchronization with cross-sectoral . While external factors include the interests of the community itself.